Designerly Ways of Knowing Internet Research: A Case for Critical Media Design - Brabham, Daren C. (AoIR Selected Papers of Internet Research, 2013)
This essay presents a case for critical media design, a methodological framework for approaching Internet studies research that blends the investments of critical theory, the practice of applied, grounded research, and a design-driven way of conceiving of problem solving in practical ways.